Multiplexed real-time and digital PCR tools to differentiate clades of Plasmopara viticola causing downy mildew in grapes - Heger, Lexi; Sharma, Nancy; McCoy, Austin Glenn; Martin, Frank N; Miles, Laura Avila; Chilvers, Martin I; Naegele, Rachel P; Miles, Timothy D (Plant disease, 2025)
In vineyards, downy mildew of grapes, caused by the oomycete pathogen , can cause significant economic losses when left unmanaged. is a species complex, made up of at least four clades, or cryptic species, causing disease on at least eight plant species within the family Vitaceae. In the United States, clades , , and , have been identified, as being present in the Great Lakes region on cultivated grapes. Within this study, a multiplexed TaqMan qPCR assay system capable of differentiating among these three taxa was developed using a mitochondrial gene order difference unique to species (cox1-atp1). The assay is needed to clearly differentiate among the closely related species as research investigates relationships between the clades and their varying hosts as well as fungicide resistance development. The multiplexed assay was validated using a panel of target and non-target samples of varying types, including leaves, ToughSpot stickers, and air sampling rods. The assay was also transferred to and optimized on a digital PCR (dPCR) platform. Air sampling rods and artificially inoculated mixed samples were tested using both qPCR and the dPCR assays to gauge utility of each. The multiplexed assays for each clade showed varying sensitivity of 10 to 1,000 fg of DNA and efficiency of 70-85% in qPCR. The dPCR sensitivity was the same, except for clade riparia, which showed a potential tenfold increase in sensitivity. These results suggest that the dPCR can serve as a more sensitive option than qPCR when trying to diagnose plant pathogens, but it is dependent on the assay. This assay system provides detection of the pathogen and classification of P. viticola clades allowing discrimination in areas growing multiple cultivated or wild grape species. This will continue to be relevant as wild hosts can potentially harbor different P. viticola clades and downy mildew is intensely managed in commercial vineyards.